Exploring contributing factors to PISA 2022 mathematics achievement: Insights from Indonesian teachers - Tommy Tanu Wijaya; Wahyu Hidayat; Neni Hermita; Jesi Alexander Alim; Corrienna Abdul Talib (Jurnal Infinity, 2024)
As an international benchmark, the Programme for International Student Assessment (PISA) 2022 evaluates the educational performance of 15-year-old students across various countries. It has been observed that the average mathematics score globally declined in 2022. Understanding the responses of mathematics teachers, as practitioners, to the PISA 2022 results is crucial for evaluating the reasons behind this decline in mathematics scores. This research aims to explore and understand the perspectives of Indonesian mathematics teachers on the factors contributing to the low PISA 2022 mathematics scores. This study employs a qualitative approach, with participants being randomly selected and includes interviews with 36 mathematics teachers in Indonesia. According to the statements provided by teachers, the decline in mathematics scores in the 2022 PISA, relative to the years 2018 and 2015, can be attributed to six primary factors: pandemic-related issues, curriculum, individual factors, resource limitations, student factors, and parental involvement. Subsequently, mathematics teachers provided several recommendations for the government, schools, and parents that might enhance student mathematics achievement. These recommendations include conducting more training, improving ICT facilities in schools, and strengthening parental knowledge about the importance of parental support. The findings of this study offer various recommendations that could be implemented by the government, schools, and mathematics teachers to improve student mathematical achievement and potentially increase PISA scores in 2025.